Medicinal plant knowledge and its erosion among the Mien (Yao) in northern Thailand - Srithi K. (2014)
Ethnopharmacological relevance: We studied local knowledge and actual uses of medicinal plants among the Mien in northern Thailand, documenting traditional medical practices and its transfer between generations. Aim of the study: With the assumption that discrepancies between knowledge and actual use represent knowledge erosion, we studied whether actual use of medicinal plants corresponded to people's knowledge of such uses. Materials and methods: We used local knowledge from four specialist informants as the domain for semi-structured interviews with 34 randomly selected non-specialist informants. We calculated informant consensus, use value, and fidelity level for each species and use category and performed statistical analyses with Kolmogorov-Smirnov tests, Pearson correlation coefficient, Spearman's rank correlation coefficient, and paired-sample t-tests. Results: We found significant discrepancies between knowledge and actual use of medicinal plants. The number of known and actually used plants increased with increasing informant age and decreased with increasing years of formal education. Conclusions: Medicinal plant knowledge and use in these Mien communities is undergoing inter-generational erosion because of acculturation and interrupted knowledge transmission. Preservation of Mien medicinal plant intellectual heritage requires continued documentation concerning use, conservation, and sustainable management of this resource, which should be publicized to younger Mien. © 2009 Elsevier Ireland Ltd. All rights reserved.